The Effect of E-Auction Service Quality on The Satisfaction of Auction Applicants at KPKNL Metro - Mazwa, Refizma Poltica; Maskanah, Ummi; Afif, Muhammad (Manunggal Halim Jaya, 2025)
This study aims to determine whether the service quality of internet-based auctions (e-Auction) has an impact on the satisfaction of auction applicants at KPKNL Metro. The research design used is a quantitative approach. The results show that the service quality of internet-based auctions (e-Auction) has a significant effect on the satisfaction of auction applicants at KPKNL Metro. The service quality of the internet auction on the satisfaction of auction applicants has a p-value of 0.000 < 0.05 and a t-value of 5.745 > t-table 2.023, indicating that H1 is accepted, meaning there is an effect of the internet auction service quality on the satisfaction of auction applicants at KPKNL Metro. The F-value of 33.006 > the F-table value of 3.24 further confirms that H1 is accepted, meaning there is a simultaneous effect of internet auction service quality (X) on auction applicant satisfaction (Y). The R Square value, or coefficient of determination, is 0.471, meaning that the effect of the independent variable (X) on the dependent variable (Y) is 47.1%. Therefore, it can be concluded that H0 is rejected, and Ha is accepted, indicating that the quality of internet auction the satisfaction of auction applicants at KPKNL Metro.